Response of groundnut (Arachis hypogaea L.) varieties to sowing dates and NP fertilizers under western dry zone of India (Bangladesh Journal of Botany, 2015)
An experiment was conducted during Kharif seasons of 2009 and 2010 on groundnut (Arachis hypogaea L.) under western dry zone of India following a split-plot design with four dates of sowing (April 20, May 15, June 9 and July 4) and two varieties (HNG 10 and TG 37A) in main- plot and four fertility levels (0, 20 N : 40 P2O5, 30 N : 60 P2O5 and 40 N : 80 P2O5 kg /ha) in sub-plot. Yield component of semispreading variety HNG 10 i.e. pods/plant, number of kernel/pod, seed index, shelling percentage and yields i.e. pod, kernel, haulm and biological yield were statistically at par with each other from April 20 to June 9 sowing and minimum yield was observed in July 4 sowing, while days to maturity reduced significantly with delay sowing. Variety TG 37A sown at July 4 had significantly higher yield attributes and yields than earlier sowing. Harvest index in both the varieties was observed significantly higher in July 4 sowing. Significantly higher yield components and yields were recorded in 30 kg N-60 kg P2O5/ha which was statistically at par with 40 kg N-80 kg P2O5/ha. On the basis of economics, June 9 sowing variety HNG 10 of groundnut recorded significantly higher net return. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21669 Bangladesh J. Bot. 43(2): 169-173, 2014 (September)